Karakteristik Gaya Tari Minangkabau Tari Mulo Pado dan Tari Benten - Wahyuni, Wahida; Yusfil, Yusfil Yusfil; Suharti, Suharti Suharti (PANGGUNG, 2018)
Abstract Minangkabau traditional dances have similarities in movement characters based on pencak silat as an identity attached to the Minangkabau dance. On the other hand, Minangkabau dance has different styles of embodiment between darek and pasisia. This paper builds upon an assumption that the Minangkabau dance style has special differences between darek and pasisia that is mostly influenced by their natural and cultural characteristics. By using the perspective of dance style and ethnography method, this paper aims to explain the  characteristic style of Minangkabau dance by taking the examples of mulo pado dance from nagari Padang Magek (darek) and benten dance from nagari Laban Pesisir Selatan (pasisia). The results show that there is a tendency of dance embodiment between the two dances which show the differences of Minangkabau dance styles in darek and pasisia.  Keywords: dances style, body, darek, pasisia, Minangkabau Abstrak Tari tradisional Minangkabau memiliki kesamaan karakter gerak yang berbasis pencak silat sebagai identitas yang melekat pada tari-tari Minangkabau. Namun, di sisi lain tari Minangkabau memiliki perbedaan gaya pembawaan antara darek dan pasisia. Tulisan ini dibangun berdasarkan asumsi bahwa gaya tari Minangkabau berbeda antara darek dan pasisia yang dipengaruhi oleh alam dan corak budaya yang berbeda. Dengan menggunakan pendekatan perspektif gaya tari dan metode etnografi, tulisan ini bertujuan untuk menjelaskan gaya tari tradisional Minangkabau dengan mengambil contoh kasus tari mulo pado dari nagari Padang Magek (darek) dan tari benten dari nagari Laban Pesisir Selatan (pasisia). Hasil penelitian mengungkap kecenderungan pembawaan tari yang berbeda antara kedua tari yang menunjukkan adanya perbedaan gaya tari Minangkabau di darek dan pasisia. Kata kunci: gaya tari, tubuh, darek, pasisia, Minangkabau,